Bundle structures inside the deep cervical lymphatic vessels of mice - Joonyoung Shin; Sungchul Kim (Scientific Reports)
Abstract The lymphatic system plays a crucial role in immune function and the removal of cellular waste. Recent studies have highlighted the presence of primo vessels (PVs) inside lymphatic vessels, distinct from conventional lymphatic tissues, yet their structural and functional characteristics remain poorly understood, particularly PVs inside deep cervical lymphatic vessels (dcLVs) connected to the meningeal lymphatics. We used a combination of Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), Alcian Blue (AB) and H&E staining techniques to identify and characterize PVs inside the dcLVs of mice. PVs were identified inside the dcLVs, revealing distinct bundle structures composed of 3 to 5 primo subvessels (sub-PV), with diameters of 5.4 ± 2.4 μm. AFM analyses confirmed the presence of nm-sized pores on the sub-PVs, which may facilitate the absorption and retention of nanoparticles. Rod-shaped nuclei were also observed, further distinguishing PVs from other vascular structures. Our study provides new insights into the structural characteristics of PVs inside dcLVs, suggesting their potential role in targeted drug delivery. However, further research is required to explore the functional implications of these structures, especially their therapeutic applications and roles in various lymphatic regions, including the meningeal lymphatics.